1981
DOI: 10.1128/iai.31.2.798-807.1981
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bile acid derivatives on taurine biosynthesis and extracellular slime production in encapsulated Staphylococcus aureus S-7

Abstract: Various bile acids were added to cultures of encapsulated strains of Staphylococcus aureus growing in serum-soft agar medium of brain heart infusion broth. We examined effects of these compounds on cellular characteristics such as growth type, cell volume index, clumping factor reaction, slime yield, taurine content, and L-(--)-cysteic acid decarboxylase activity. Upon addition to the medium of either taurochenodeoxycholic acid, taurocholic acid (25 to 50 microgram/ml), or cholic acid (10 to 25 microgram/ml), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…We have already reported that CSP is inhibited by hightemperature cultivation (13) or the addition of bile acid derivative (12,20). Loss of CSP because of freeze-drying is an important issue because it affects the maintenance of morphological stability during the preservation of microorganisms (1,8,26,29).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have already reported that CSP is inhibited by hightemperature cultivation (13) or the addition of bile acid derivative (12,20). Loss of CSP because of freeze-drying is an important issue because it affects the maintenance of morphological stability during the preservation of microorganisms (1,8,26,29).…”
Section: Discussionmentioning
confidence: 99%
“…Microorganism. An encapsulated strain of S. aureus, S-7 (Smith diffuse), was selected for this study (18,20). Strain * Corresponding author.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations